TINJAUAN YURIDIS TERHADAP MEREK NEUROBION DAN BIONEURON BERDASARKAN PUTUSAN NOMOR : 409K/Pdt. Sus-HKI/2015 - Sembiring, Desi Milasari; T.M., S. Tirtasari; Apriyani, Wulandari (Legal Standing : Jurnal Ilmu Hukum, 2021)
IPR is part of the brand which stands for Intellectual Property Rights. The function of a mark is to give a marker or indicate a distinguishing power which is intended so that a service or goods in a company can be identified. Similarly, the Neorobion and Bioneuron brands involved in the brand dispute case in this study. The purpose of this study is to analyze legal arrangements, legal protection and judges' considerations in deciding disputes against Judges' Decisions related to the case of the Neurobion and Bioneuron brand disputes. This research applies normative juridical research method which is descriptive analytical. The results of this study are based on a document study of the decision of the Supreme Court (MA) and an analysis of the laws and regulations. Based on the Trademark Law Regulations, it is explained that in carrying out trademark registration, substantive and formal requirements must be met. Furthermore, in this study, it is explained that legal protection for trademark ownership rights is constitutive, namely the first registrant system, and based on the analysis of the Decision it is explained that the Supreme Court's decision has been deemed correct and does not contradict the law, namely canceling the ownership rights of the Bioneuron Mark which registered its trademark on the basis of bad faith. because the brand has similarities and similarities in principle and in its entirety with the neurobion brand that has been previously registered so that it can mislead consumers and cause harm to the Neurobion brand.